Biliary atresia: graft-versus-host disease with maternal microchimerism as an etiopathogenesis. (April 2022) - Masuya, Ryuta; Muraji, Toshihiro; Harumatsu, Toshio; Muto, Mitsuru; Nakame, Kazuhiko; Nanashima, Atsushi; Ieiri, Satoshi
Abstract: Biliary atresia (BA) is an inflammatory disease of the biliary system in newborns and infants. The etiology is largely unknown. Approximately half of BA patients require liver transplantation by 20 years of age, even after surgical correction due to progressive fibrosis of the liver. Regarding the disease mechanism, there is circumstantial evidence to support the hypothesis of graft-versus-host disease because of the existence of maternal cells in the liver (maternal microchimerism, MMC), histopathological similarity of the liver and an intense maternal response to the BA patient with mixed lymphocyte culture. Immune dysregulation with decreased Treg and increased Th1 and Th17 cells are the pathogenic features of BA, which are homologous to the pathogenic features of GvHD. Further elucidation of the etiopathogenetic mechanism of BA is warranted for development of new therapeutic strategies for native liver survival.